Validity of the E-Module Learning Cycle 5E Integrating Local Potential in Integrated Science Education for Equity Education - Hamdani Hamdani; Rizka Donny Agung Saputra (Postgraduate, University of Mataram, 2024)
Education plays a strategic role in improving human resources and ensuring equal access to quality learning for all members of society, including learners in nonformal education settings. This study aims to develop an E-Module Learning Cycle 5E that integrates local potential into integrated science learning at the Nonformal Education Unit (SPNF) Sanggar Kegiatan Belajar (SKB) Boto, Sumbawa Barat. Recognizing that education is a fundamental right of every citizen and that the challenges in equitable education include the lack of teaching materials suitable for the characteristics of learners, this research employs the Research & Development (R&D) method to produce a valid and relevant product. The development process involves evaluation by experts on four main aspects: Learning, Quality, Function, and Appearance. The validation results indicate that this E-Module has good validity, with average ratings supporting its effectiveness in enhancing independent learning motivation and learners' understanding. However, there are several aspects that need improvement, including the addition of interactive activities and enhancement of visual design. With these improvements, it is hoped that the E-Module can contribute positively to equitable education and the development of local potential in the region